Metode dan Strategi Penerjemahan Bahasa Arab ke Bahasa Indonesia pada Subtitle Film “Ar Risalah” - Linda Dwi Nofiyani; Ade Kosasih; Tubagus Chaeru Nugraha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study discusses the application of translation methods and strategies in the subtitles of the film Ar Risalah from Arabic to Indonesian. The film Ar Risalah is a religious film that tells the story of the life of the Prophet Muhammad SAW, which has strong historical and cultural values. This study aims to identify the methods and strategies used in translating dialogue sentences in the film's subtitles. Using a qualitative descriptive research method, data were collected through direct observation of the film's dialogue. The researcher classified the translation methods based on Newmark's theory and translation strategies from Pamungkas and Akmaliyah. The results of the study showed that there were seven translation methods used, namely word-for-word, literal, faithful, semantic, adaptation, free, and idiomatic translation. In addition, there were four translation strategies, namely prioritizing and ending, reducing, adding, and replacing. These findings indicate that translators must consider lexical, contextual, and cultural aspects in producing translations that are communicative and in accordance with the target language. This study provides in-depth insight into the complexity of the film translation process, which is expected to be a reference for subtitle translators in the future.